A new 3-D mesh simplificatión algorithm - Xianfeng, Wu; Jianhui, Ye (Revista Colombiana de Computación, 2003)
To simplify the 3D color head mesh ,it is more important to keep the boundary and quality of the head’s sense organs including eyes, eyebrows, nose and mouth. In this paper, we present a novel mesh simplification algorithm based on region segmentation. The algorithm can be divided into two stages: segmentation and simplification. After the automatic segmentation of 3D color head mesh into different head parts, vertices are classed into region-boundary vertices and region-inner vertices. Using iterative edge collapse and region-weighted error metric, the algorithm generates continuous levels of detail (LOD). Results of several experiments are shown, demonstrating the validity and efficiency of our method. Keywords: mesh simplification, level of detail, image segmentation, multi-resolution model